A Brewster route to Cherenkov detectors - Xiao Lin (Nature Portfolio, 2021)
Cherenkov detectors are used to detect high energy particles and their performance capabilities depend heavily on the material used. Here, the authors propose use of a Brewster-optics-based angular filter for a detector with increased sensitivity and particle identification capability.